OPTIMISING GOOGLE SCHOLAR INDEXATION: A STRATEGY TO IMPROVE LECTURERS' ACADEMIC REPUTATION - Novianty Djafri (International Journal of Teaching and Learning, 2025)
This study aims to analyse the effect of optimising Google Scholar indexation on improving the academic reputation of lecturers. The method used is literature. The results showed that the use of relevant keywords, regular profile updates, and managing references with reference management applications contributed significantly to increasing the visibility and citation of lecturers' academic work. This has a positive impact on individual and institutional reputation. This research suggests that modern academic activities should embrace indexation technology to increase global scholarly reach and influence, as well as strengthen professional networks within the academic community.